Crystallization and phase separation mechanism of silicon oxide thin films fabricated via e‐beam evaporation of silicon monoxide. Issue 9 (9th November 2015) - Gunduz, Deniz Cihan; Tankut, Aydin; Sedani, Salar; Karaman, Mehmet; Turan, Rasit
Abstract: In this work, silicon oxide thin films were synthesized via e‐beam evaporation of silicon monoxide. Subsequent annealing experiments were carried out to induce Si nanocrystals (Si NCs) formation. A broad range of annealing durations and temperatures were studied. Raman spectroscopy, X‐ray photoelectron spectroscopy (XPS) and Fourier Transform Infrared Spectroscopy (FTIR) were employed to study the mechanism of phase separation in silicon oxide films and crystallization of Si. Raman spectroscopy results show that SiO cannot be considered as a composite mixture of Si and SiO2 . Results suggest that phase separation and crystallization are two separate processes even at relatively high temperatures. Amorphous Si formation was observed at annealing temperatures as low as 800 °C. A minimum annealing temperature of between 800 and 900 °C is required to form Si NCs. XPS results show a strong phase separation at annealing temperature of 1100 °C. (© 2015 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)